Addressing Educated Unemployment in Padang City: Data Analysis, Theory, and Policy Recommendations - Putra, Ferrid Syaf (Jurnal Ilmiah Ekotrans & Erudisi, 2025)
This study addresses educated unemployment in Padang City by integrating official labor-market statistics with a theory-informed policy diagnosis. Using recent Sakernas-based indicators and provincial/city benchmarking, the analysis documents that Padang’s unemployment level is among the highest in West Sumatra and that joblessness is disproportionately concentrated among upper-secondary and tertiary-educated groups, indicating persistent frictions in education-to-work transitions. The results suggest that the problem is shaped by interacting mechanisms: limited availability of graduate-appropriate jobs within a service- and microenterprise-dominated economy, substantial informality that absorbs labor but weakly supports high-skill career ladders, and matching inefficiencies consistent with skill mismatch, overeducation risk, and credential competition. Building on these findings, the paper proposes a targeted policy package that combines demand-side job upgrading and sector-oriented job creation with supply-side improvements in skills signaling, employer-linked training, structured internships/apprenticeships, and strengthened labor-market intermediation. The study contributes a city-focused evidence base to guide local government and education institutions in designing measurable, implementable interventions to reduce educated unemployment and improve job quality.